Effect of Solid-Phase Modification of High-Modulus Zeolite TsVM with Cerium Oxide in Conversion of Bioethanol to Hydrocarbons - Mammadov, E.S.; Kerimli, F.Sh.; Akhmedova, N.F.; Mammadov, S.E.; Mirzaliyeva, S.E. (Karagandy University of the name of academician E.A. Buketov, 2025)
The catalysts used for the conversion of bioethanol into hydrocarbons were obtained by solid-phase modification of high-modulus zeolite HTsVM (SiO2:Al2O3 = 40) of the ZSM-5 type with cerium carbonate followed by heat treatment at 550 °C for 4 hours. The reactions were carried out in a flow reactor with a fixed catalyst bed in the temperature range of 300–450 °C at atmospheric pressure in order to study the effect of cerium oxide concentration in the HTsVM on its selectivity for isomerization and aromatization products. The modification of zeolite HTsVM with cerium oxide was shown to result in a change in its structural and acidic characteristics, as well as its selectivity for cracking, isomerization and aromatization reactions. The isomerisation selectivity of a catalytic system based on zeolite ZSM-5 can be increased by modifying it with rare earth or transition metals, which gives the catalyst a bifunctional character. This increase in isomerisation selectivity and decrease in aromatization selectivity are due to a significant reduction in the density of strong acid sites, the formation of additional Lewis cation sites and a decrease in total pore volume, as well as an increase in mesopore volume. The optimal 3 % CeO􀎍/HTsVM catalyst demonstrates high stability (30 hours) and high selectivity for isomerization products (44.90–46.06 %) within the temperature range of 300–350 °C. The gasoline fraction obtained using the 3 % CeO2/HTsVM catalyst at 300 °C is enriched in isoparaffinic hydrocarbons (48.73 wt.%) and complies with the Euro 5 standard with regard to aromatic hydrocarbon content (21.17 wt.%) and benzene content (<1.0 wt.%).
Keywords: zeolite TsVM; cerium oxide; modification; selectivity; isomerization; aromatization; catalyst; surface; porosity; acid centers; bioethanol